Identification and Expression Patterns of Three Vitellogenin Genes and Their Roles in Reproduction of the Alligatorweed Flea Beetle Agasicles hygrophila (Coleoptera: Chrysomelidae) - Zhang, Hong; Wang, Yao; Liu, Yiran; Zhao, Meiting; Jin, Jisu; Zhou, Zhongshi; Guo, Jianying (Frontiers in Physiology, 2019)
The alligatorweed flea beetle Agasicles hygrophila is an insect used for biological control of the aquatic weed Alternanthera philoxeroides (alligatorweed). Because these insects are oviparous, synthesis and transportation of yolk proteins is integral to reproduction. Vitellin, the chief protein constituent in egg yolk, is mainly synthesized in the fat body and its synthesis is regulated by the transcript levels of Vitellogenin (Vg). In our study, we first cloned and characterized three Vg genes from A. hygrophila and quantified the expression levels of these Vgs in different tissues and developmental stages by RT-qPCR. Analysis of the full-length cDNA sequences of the three A. hygrophila Vg genes revealed that the open reading frames of AhVg1, AhVg2, and AhVg3 were 5175 bp, 5346 bp, and 5385bp, encoding 1724, 1781, and 1794 amino acids, respectively. RT-qPCR analysis revealed that these three AhVgs have similar expression patterns; expression in the fat body was significantly higher than that in other tissues, and the highest expression was observed in the adult developmental stage. RNA interference was used to explore the functions of the AhVgs. A. hygrophila female adults injected with dsRNA targeting the AhVg genes showed decreased AhVg gene expression. Down regulation of all three AhVgs significantly affected ovary development, reduced egg laying capacity, and reduced the egg hatch rate compared with the control groups. Our findings provide the basis for further study of the functions of Vg genes in other insect species.